Effect of noise, partial synchronization, and sampling frequency inaccuracies on amplitude measurement of multiple linear chirp signals. (August 2021) - Moschitta, Antonio; Comuniello, Antonella; De Angelis, Alessio; Santoni, Francesco; Carbone, Paolo
Highlights: Amplitude estimation of multiple superimposed chirp signals is analyzed. Effects of chirp pulse length and bandwidth is investigated. Effects of sampling frequency mismatch is theoretically modeled. Effect of uniform quantization is considered. Performance requirements are assessed. Abstract: In this paper, simultaneous amplitude measurement of multiple Linear Chirp Signals (LCSs) is discussed, with the main aim of supporting the development of tracking systems based on Received Signal Strength measurements, capable of tracking multiple targets. LCSs are assumed to be generated by digital devices whose clocks are not fully synchronized. Effects of partial synchronization and noise at the receiver side are investigated and discussed, assuming that the signals' amplitudes are estimated using correlation techniques. Moreover, effect of quantization is discussed, and the effects of a mismatch in the sampling frequency of LCSs feeding the estimation algorithm are deeply analyzed and modeled. It is shown that using interpolation techniques does not significantly improve the estimation accuracy. Moreover, in the presence of frequency mismatches using long LCSs does not lead to increased accuracy. Finally, frequency accuracy of currently available microcontroller units may permit practical implementations of the proposed solution.